Penggunaan Media History Timeline Digital Untuk Meningkatkan Kemampuan Berpikir Kronologis di Kelas XI IPS 4 Sma N 2 Lembang - Ananda, Dava (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
The research was conducted based on the background of the low chronological thinking ability of students in class XI Social 4 of SMA N 2 Lembang. Given these problems, the researcher aims to improve students' chronological thinking skills in learning history by using learning media, namely digital history timeline media. The ability to think chronologically is one of the stages of mastering the ability to think historically. Where the ability to think chronologically becomes so important because it is the initial stage in the ability to think historically. That way, the ability to think chronologically becomes so important to be understood and mastered by students in learning history. planning (Plan); implementation (Act); observation (Observing); and reflection (reflection). This research was conducted in IX cycles. Where in each cycle the results obtained have increased. In cycle I the percentage obtained was 45.8%, then in cycle II it increased to 60.4%, cycle III decreased to 58.3%, cycle IV increased again to 68.8%, cycle V 78.2 %, in cycle VI it was 89.6%, in cycle VII it again decreased to 85.4%, and increased again in the last two cycles, namely 93.7% for cycle VIII and 95.8% for cycle IX. Judging from the research results obtained, the ability to think chronologically can be said to increase through the use of digital timeline history media as learning media.